The Future of our Democracies - Bruter, M. author. aut Link
XII, 250 p.
Keywords: This book presents the results of a new comparative research project on the trajectories, motivations, perceptions and attitudes of young members (aged 18-25) of 15 different European political parties in the UK, France, Germany, Spain, Norway and Hungary. The project combined a mass survey of 2919 young party members with 517 in-depth interviews.